Long-term Results from the Empowering a Multimodal Pathway Toward Healthy Youth Program, a Multimodal School-Based Approach, Show Marked Reductions in Suicidality, Depression, and Anxiety in 6,227 Students in Grades 6–12 (Aged 11–18) - Silverstone, Peter H.; Bercov, Marni; Suen, Victoria Y. M.; Allen, Andrea; Cribben, Ivor; Goodrick, Jodi; Henry, Stu; Pryce, Catherine; Langstraat, Pieter; Rittenbach, Katherine; Chakraborty, Samprita; Engles, Rutger C.; et al. (Frontiers in Psychiatry, 2017)
Here we report on findings from a 15-month follow-up of a school-based program called Empowering a Multimodal Pathway Towards Healthy Youth (EMPATHY). This was primarily intended to reduce suicidal thinking in pre-teens, adolescents, and youth students aged 11-18 in Middle Schools (Grades 6-8) and High Schools (Grades 9-12). It also aimed to reduce depression and anxiety. The EMPATHY multimodal program consisted of repeated data collection, identification of a high-risk group, a rapid intervention for this high-risk group including offering supervised on-line CBT program, a universal CBT intervention for those in Grades 6-8, a variety of interactions with trained staff (“Resiliency Coaches”), and referral to external medical and psychiatric services where appropriate. There were four time-points at which assessments were made: Baseline, 3-months, 7-months, and 15-months. Here we report cross-sectional findings over 15-months in a total of 6,227 students who were assessed at least once during the study period. Additionally, we report longitudinal findings from the 1,884 students who completed all 4 assessments. Our results found highly statistically significant decreases in suicidality rates, with the percentage of the total school population who were actively suicidal decreasing from 4.4% at baseline (n=143 of 3,244) to 2.8% at 15-months (n=125 of 4,496) (p<0.001). There were also highly statistically significant reductions in depression and anxiety scores at each time point. Thus, mean depression scores at baseline for the entire student population were 3.73 ± 3.87 (n=3,244) at baseline and decreased to 3.22 ± 3.52 (n=4,496) (p<0.001). Since most students were not depressed, whole population changes such as this may indicate impact in many areas. In the longitudinal analysis of students who completed all 4 assessments there were also highly statistically significant improvements in depression and anxiety scores at all time points. For example, depression scores decreased from a mean of 3.43 ± 3.67 (n=1,884) at baseline to 2.95 ± 3.53 (n=1,884) at 15-months (p<0.001), while the number who were actively suicidal decreased from 69 to 37. These results suggest that school-based multimodal programs, utilizing a combination of interventions, can have meaningful benefits across entire school populations.